Strategi pemasaran pada usaha Batik Jambi - Dahmiri, Dahmiri; Kartika Wulan Bhayangkari, Sylvia (Jurnal Paradigma Ekonomika, 2023)
This study aims to analyze the marketing strategy of the Jambi Siti Hijir batik business in Jambi City. The number of informant in the study were 10 people, namely 1 business owner, 3 employees, 3 residents and 3 consumers who had made a purchase. Collecting research data using the interview method with informants using a previously prepared guide. In order to complete the research data, primary and secondary data were taken. The primary data of the study were taken through interviews and observations of Jambi batik business actors by visiting the business location directly, while secondary data was obtained from various literatures and reports from related institutions. Processing research data using qualitative methods with the analytical tools used are internal analysis, external analysis with a SWOT matrix. The conclusion of the study is that Siti Hijir's Batik Jambi business marketing strategy can be carried out by supporting aggressive marketing growth policies (Growth Oriented Strategy) such as: rational pricing policies, vigorous promotion through social media, improving product packaging, increasing business capital, increasing capacity production, increase human resource capabilities and respond quickly to customer complaints